Forces at the eeet, gait timing, and trunk flexion/extension excursion while walking with a gear belt or gear vest load - Maher, S. S.; Dill, L. L.; Hein, J. L.; Nessler, J. A.; Schmidt, D. J. (International Journal of Exercise Science, 2022)
Law enforcement personnel often carry gear loads, which have a history of causing low back pain. The aim of this study was to evaluate the differences in gait and trunk posture for gear load carried on a gear belt and a gear vest. Twenty-nine participants performed load carriage in three conditions: a no load control trial (C), a symmetrically loaded gear belt (GB), and an anterior-loaded gear vest (ALV). Gear conditions had 9.07 kg of additional mass. Motion capture and insole force sensors were used to collect data while participants walked on a treadmill for three minutes per condition. Mean insole reaction force was significantly greater in both GB and ALV conditions as compared to C (p < 0.001). Mean gait cadence in the GB or ALV condition were not significantly different from the C condition. However, double support time in the ALV condition was significantly longer compared to C condition (p = 0.023). Stance duration on the left foot was significantly longer with the GB (p = 0.001) and ALV (p = 0.028) when compared to C. Results showed trunk flexion/extension excursion was significantly less in the GB condition when compared to the C condition (p = 0.002). These findings demonstrate that law enforcement and other personnel who walk while carrying gear loads may experience altered biomechanics compared to unloaded walking. Altered biomechanics and increased forces on the feet could potentially increase risk of musculoskeletal injury while carrying gear loads.